2018
DOI: 10.2147/cmar.s171200
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cadmium exposure aggravates malignant phenotypes of nasopharyngeal carcinoma by activating the Wnt/β-catenin signaling pathway via hypermethylation of the casein kinase 1α promoter

Abstract: BackgroundOur previous study has shown that cadmium (Cd) exposure is not only a risk factor for nasopharyngeal carcinoma (NPC), but also correlated with the clinical stage and lymph node metastasis. However, the underlying molecular events of Cd involved in NPC progression remain to be elucidated.PurposeThe objective of this study was to decipher how Cd impacts the malignant phenotypes of NPC cells.MethodsNPC cell lines CNE-1 and CNE-2 were continuously exposed with 1 μM Cd chloride for 10 weeks, designating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
2
13
0
2
Order By: Relevance
“…Therefore, Cd can easily enter into the food chain or efficiently transfer to plants [9]. This toxic heavy metal has many adverse health effects [10] and studies have suggested that Cd induced different types of cancers [11, 12], liver- and renal dysfunction [13], diabetes and cardiovascular diseases [14]. In diabetes, it exacerbates beta cell dysfunction and studies showed varied results [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Cd can easily enter into the food chain or efficiently transfer to plants [9]. This toxic heavy metal has many adverse health effects [10] and studies have suggested that Cd induced different types of cancers [11, 12], liver- and renal dysfunction [13], diabetes and cardiovascular diseases [14]. In diabetes, it exacerbates beta cell dysfunction and studies showed varied results [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β-catenin pathway has also been investigated in nasopharyngeal carcinoma cell lines exposed to cadmium. In this study chronic low-dose Cadmium enhanced malignant progression, including more proliferative and aggressive characteristics through the activation of the Wnt/β-catenin pathway and DNA methylation (Peng et al, 2019).…”
Section: Effects Of Edcs On Wnt Pathwaymentioning
confidence: 95%
“…Izloženost kadmijumu je povezana sa karcinomom nasofaringsa, pluća, pankreasa,jetre, bubrega, dojke, prostate i mokraćne bešike u ljudi 9,10,11 . Zbog toga su Internacionalna Agencija za Istraživanje Kancera (International Agency for Research on Cancer) i Nacionalni Toksikološki Program SAD (National Toxicology Program of the USA) svrstali kadmijum u grupu humanih karcinogena I kategorije 11,12 .…”
Section: Uvodunclassified
“…U ljudi kadmijum najčešće ulazi u organizam inhalacijom,preko digestivnog trakta i preko kože.Kada dospe u cirkulaciju kadmijum se transportuje do depoa, Ranije se smatralo da se oko 50% kadmijuma akumulira samo u jetri, bubrezima ili mišićima, međutim ispitivanja koncentracija kadmijuma u štitastoj žlezdi u bolesnika obolelih od "itai itai" su pokazala da se tkivna koncentracija kadmijuma u tireoideji, kod muškaraca, nalazi na drugom mestu, iza koncentracija kadmijuma u jetri, a kod žena na trećem mestu, iza jetre i pankreasa 13 . Kadmijum se eliminiše iz organizma urinom i preko digestivnog trakta, ali zbog prekomerne akumulacije u krvi i u depoima i male ekskrecije on ima biološki poluživot čak od 15-40 godina 9 . Procenjeno je da više od 80% kadmijuma koji se unese hranom dolazi od cerealija, povrća i paradajiza 14 .…”
Section: Diskusijaunclassified